Effect of Carrot-Juice on Exopolisaccharides and Î²-D Galactosidase Activity in Yogurt - Radiati, Lilik Eka; Jaya, Firman; Oktavia, Heldy (ANIMAL PRODUCTION, 2016)
Carrot juice and milk Â were Â blended and fermented by Â culture bacteria Streptococcus thermophillus Â and Lactobacillus bulgaricus. Â Carrot juice Â affect significantly Â on Â  lactic acid content Â  (1.09Â± 0.12% â 1.15Â± 0.01%), Â  pH value (3.80Â±0.06 â 4.17Â± 0.10), Â  viscosity Â (133Â±2.30 cPâ146Â±2.10cP), Â Î²-carotene (0-173.19Â±1.02 Âµg/g), EPS (11.90 Â±0.50 - 18.00 Â±0.40 mg/100g), Â  Î²-D-galactosidase activity (2.27Â±0.30-192.40Â±0.48 Âµ/g) yogurt, but did not affect significantly on Â bacteria number (9.0Â± 0.5 â 9.8Â±0.4 log CFU/g). Â  Â Carrot juice increased the yogurt culture activity with increasing acidifying, Î²-catotene, EPS and Î²-D-galactosidase, suggesting that yogurt could be fortified with carrot juice.